2014
DOI: 10.1007/s00125-014-3464-9
|View full text |Cite
|
Sign up to set email alerts
|

MafA is critical for maintenance of the mature beta cell phenotype in mice

Abstract: Aims/hypothesis The plasticity of adult somatic cells allows for their dedifferentiation or conversion to different cell types, although the relevance of this to disease remains elusive. Perturbation of beta cell identity leading to dedifferentiation may be implicated in the compromised functions of beta cells in diabetes, which is a current topic of islet research. This study aims to investigate whether or not v-Maf musculoaponeurotic fibrosarcoma oncogene family, protein A (MafA), a mature beta cell marker, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 41 publications
6
89
1
1
Order By: Relevance
“…adult mature b-cells at least in mice (Nishimura et al 2006, Artner et al 2010. Using MafB reporter mice (Moriguchi et al 2006), we previously reported that the MafB promoter was upregulated in b-cells of the diabetic model mice (Nishimura et al 2015). The present study suggests the possibility that MafB upregulation in compromised b-cells in vivo may also be at least in part due to lower methylation status of the MafB promoter.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…adult mature b-cells at least in mice (Nishimura et al 2006, Artner et al 2010. Using MafB reporter mice (Moriguchi et al 2006), we previously reported that the MafB promoter was upregulated in b-cells of the diabetic model mice (Nishimura et al 2015). The present study suggests the possibility that MafB upregulation in compromised b-cells in vivo may also be at least in part due to lower methylation status of the MafB promoter.…”
Section: Discussionsupporting
confidence: 53%
“…1C). The increased transcriptional activity of MafB is also similar to the b-cells in diabetic model mice (Nishimura et al 2015).…”
Section: Upregulation Of Mafb In the Late-passage Ins1 Cells A Comprmentioning
confidence: 59%
See 1 more Smart Citation
“…This knowledge will pave the way toward the development of new therapeutic approaches to prevent or reverse the progressive loss of functional β cell mass in patients with type 2 diabetes (T2D). In this issue, studies from the laboratories of Sussel (8), Dor (9), and Stoffers (10) collectively reinforce the consensus view that the same TFs that direct β cell specification are also required to maintain the gene activation and repression programs that undergird mature β cell identity (11)(12)(13)(14)(15). This unexpected property of the murine and human β cell transcriptional network provides an additional explanation for the intrinsic fragility, sensitivity (16), and propensity of these cells to adopt alternate endocrine cell fates as a consequence of various stressors (2,4,17).…”
mentioning
confidence: 88%
“…[3,4] It is noted that MafA and PDX-1 are very important transcription factors for insulin gene in mature β-cells. [3][4][5][6][7][8][9][10][11][12] Furthermore, antioxidant treatment protects β-cells from glucose toxicity in various diabetic model animals; β-cell mass and insulin content are preserved by antioxidant treatment. [13,14] In addition, expression levels of MafA and PDX-1 are decreased by oxidative stress and those expression levels are preserved by antioxidant treatment.…”
mentioning
confidence: 99%